2020
DOI: 10.15585/mmwr.mm6918a1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Self-Reported Hypertension and Antihypertensive Medication Use by County and Rural-Urban Classification — United States, 2017

Abstract: In 2017, approximately one in three U.S. adults reported having been told by a health care professional that they had high blood pressure (hypertension) (1). Although hypertension prevalence is well documented at national and state levels, less is known about rural-urban variation and county-level prevalence. To examine prevalence of self-reported hypertension and antihypertensive medication use by rural-urban classification and county, CDC analyzed data reported by 442,641 adults aged ≥18 years who participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 9 publications
1
35
1
Order By: Relevance
“…Because of the high rates of risk factors for severe COVID-19 illness in rural populations, specifically older age (60 and older), and younger adults with heart disease, cancer, chronic obstructive pulmonary disease (COPD), or diabetes, it is projected that 50% of noninstitutionalized rural adults are at high risk for hospitalization and serious illness if they are infected with COVID-19, compared to 46.9% and 40% of micropolitan and metropolitan adults, respectively [ 15 ]. While similar rates of asthma have been found in rural versus urban areas (e.g., Ownby et al [ 16 ]), hypertension [ 17 ], and obesity and overweight [ 18 ] are found to be more common in rural than urban areas. The Centers for Disease Control (CDC) also recently added asthma, hypertension, and obesity and overweight to risk factors for severe COVID-19 illness [ 19 ].…”
Section: Introductionmentioning
confidence: 68%
“…Because of the high rates of risk factors for severe COVID-19 illness in rural populations, specifically older age (60 and older), and younger adults with heart disease, cancer, chronic obstructive pulmonary disease (COPD), or diabetes, it is projected that 50% of noninstitutionalized rural adults are at high risk for hospitalization and serious illness if they are infected with COVID-19, compared to 46.9% and 40% of micropolitan and metropolitan adults, respectively [ 15 ]. While similar rates of asthma have been found in rural versus urban areas (e.g., Ownby et al [ 16 ]), hypertension [ 17 ], and obesity and overweight [ 18 ] are found to be more common in rural than urban areas. The Centers for Disease Control (CDC) also recently added asthma, hypertension, and obesity and overweight to risk factors for severe COVID-19 illness [ 19 ].…”
Section: Introductionmentioning
confidence: 68%
“…This would not explain the higher prevalence of CVD risk factors we observed because rural-dwelling adults consistently experience worse CV health and increased CVD risk factors compared with urban adults independent of race. [21][22][23][24] The Jackson Heart Study (JHS) is a contemporary, prospective, community-based cohort of AA adults designed to investigate CVD risk factors. 25 We again observed higher prevalence of CVD risk factors in our participants compared with the JHS, including current smoking (25% vs 13%), hyperlipidemia (47% vs 33%), and diabetes (34% vs 19%).…”
Section: Discussionmentioning
confidence: 99%
“…The adverse impacts of existing health disparities for people living in rural areas continue to be a major source of concern during preparation for and response to widespread disasters. Rural residents, across all racial/ethnic groups, are at greater risk from the five leading causes of death, including heart disease, cancer, unintentional injury, chronic lower respiratory disease, and stroke, compared with urban Americans [11][12][13]. Behavioral risk factors for hypertension, diabetes, and COPD such as obesity, poor nutrition, smoking, and alcohol consumption, are also higher in rural areas than non-rural places [14,15].…”
Section: Underlying Health Vulnerability and Response Disparities Between Rural And Urban Placesmentioning
confidence: 99%